Defining city boundaries through percolation theory: the case of the mexican urban system - Tapia-McClung, Rodrigo; Montejano-Escamilla, Jorge Alberto; Caudillo-Cos, Camilo Alberto (Economía Sociedad y Territorio, 2023)
We applied an emerging methodology involving percolation theory and fractal dimension to the Mexican national road network to determine cities’ boundaries in a more automated and less subjective manner. The percolated network at the distance where the maximum fractal dimension occurs, corresponds to actual built-up environmental data derived from different sources. The relationship between the critical point of the system and what is defined as urban, seems promising for defining city limits, metropolitan or functional urban areas, and dynamics related to people concentration in geographies.